The effectiveness of forest onion Eleutherine bulbosa simplisia to prevent Streptococcus agalactiae infection on Nile tilapia Oreochromis sp. - Istiqomah, Amalia; Widanarni, Widanarni; Yuhana, Munti (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
Forest onion potentially acts as an immunostimulant, enhancing the immune response of tilapia to pathogen infection. This study aimed to evaluate the effectiveness of forest onion simplisia on growth performance, immune response, and resistance of tilapia to Streptococcus agalactiae infection. The research was divided into in vitro and in vivo tests. In vitro testing was conducted to determine the dose of forest onion extract inhibiting the growth of S. agalactiae with seven treatments, namely positive control, negative control, addition of forest onion extract at 0.625, 1.25, 2.5, 5, and 10 mg/mL. In vivo testing to evaluate the administration of forest onion simplisia through feed in enhancing growth performance, immune response, and resistance of tilapia to S. agalactiae. Tilapia with an average weight of 7.57 ± 0.26 g were maintained in glass aquariums sized 60×30×30 cm3 with 15 units at a density of 15 fish/aquarium for 30 days. Experimental treatments included maintaining tilapia with the addition of forest onion simplisia at 12.5, 25, and 50 g/kg feed, negative and positive controls. The results showed that the addition of 12.5 g/kg simplisia significantly increased growth which was significantly different from the other treatments, while the immune response and resistance to S. agalactiae in all simplisia treatments showed values that were not different, but significantly different from the control treatment. The conclusion is supplementation of forest onion simplisia at a dose of 12.5 g/kg effectively enhances growth performance, immune response, and resistance of tilapia to S. agalactiae infection. Keywords: forest onion, immunostimulant, Nile tilapia, Streptococcus agalactiae ABSTRAK Bawang hutan berpotensi sebagai imunostimulan yang dapat meningkatkan respons imun ikan terhadap infeksi patogen. Penelitian ini bertujuan mengevaluasi efektivitas simplisia bawang hutan terhadap kinerja pertumbuhan, respons imun dan resistansi ikan nila terhadap infeksi Streptococcus agalactiae. Penelitian terbagi menjadi pengujian in vitro dan in vivo. Pengujian in vitro dilakukan untuk menentukan dosis ekstrak bawang hutan dalam menghambat pertumbuhan bakteri S. agalactiae dengan delapan perlakuan yaitu kontrol positif, kontrol negatif, penambahan ekstrak bawang hutan 0,625,1.25, 2,5, 5, dan 10 mg/mL. Adapun pengujian in vivo untuk mengevaluasi pemberian simplisia bawang hutan dalam meningkatkan kinerja pertumbuhan, respons imun, dan resistansi ikan nila terhadap S. agalactiae. Ikan nila berukuran 7,57 ± 0,26 g dipelihara pada akuarium berukuran 60×30×30 cm3 sebanyak 15 unit dengan kepadatan 15 ekor/akuarium selama 30 hari. Perlakuan uji meliputi pemeliharaan ikan nila dengan penambahan simplisia bawang hutan 12.5, 25, dan 50 g/kg pakan, kontrol negatif dan positif. Hasil penelitian menunjukkan penambahan simplisia 12,5 g/kg signifikan meningkatkan pertumbuhan yang berbeda nyata dengan perlakuan lainnya, adapun respons imun dan resistansi terhadap S. agalactiae pada semua perlakuan simplisia menunjukkan nilai yang tidak berbeda, akan tetapi berbeda nyata dengan perlakuan kontrol. Kesimpulan penelitian ini adalah suplementasi simplisia bawang hutan 12,5 g/kg efektif meningkatkan kinerja pertumbuhan, respons imun, dan resistansi ikan nila terhadap S. agalactiae. Kata kunci: bawang hutan, ikan nila, immunostimulan, Streptococcus agalactiae